Projeto Identicidade: espaço, identidade e fotografia - Glauber Bedini de Jesus (Confins)
The goal of this study is to evoke and to illuminate the similarities among the topics of space, identity and photography, starting from a research of conceptual guidelines, grounded in multidisciplinary studies, in which geography, philosophy, sociology and literature come together, allowing for the creation of a representative iconographic product. The construction of such visual element was made possible through the creation and revisitation of monochromatic photographic images of key locations across the cities visited by the researcher that were analyzed, organized and arranged in a way as to create a self-portrait. Even though we can notice a close relation among the themes that were researched throughout the creation process, the product entitled “Projeto Identicidade” allowed for the construction of a space/time fundamentally processual, revealing the obstacles of creating an identity from visual elements, where the hermetic quality of the technologic processes are a constant presence and, in some cases, can shape an artistic action. Parallel to that, the project also highlighted the inability to visually represent the subject’s identity through a reading of the living spaces, since these spaces become part of the landscape once they are treated as photographic images and, as such, are nothing but transtemporal interpretations of life, voided of an organic content. On the other hand, the process of creating a visual identity paved the way for revisiting and reinterpreting the life experiences within the spaces depicted in the photographies, which allowed for a deeper reflexion on the contemporary position in space, developing in a constructive and qualitative manner the researcher’s identity.